Analisis Pengelolan dan Perlakuan Aset Desa Menurut Prinsip Akuntansi Syariah di Desa Blumbungan - Holifin Holifin; Ach. Baiquni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to examine the management and treatment of village assets, located in Blumbungan Village, through the lens of the principles of prohibition, inspection, and sharia accounting. This study uses a field methodology (Qualitative). Through interviews, this study obtains direct data from the field sourced from several specific informants consisting of religious figures and including Blumbungan Village officials consisting of: Village Head, Village Secretary, Village Treasurer, Head of Kaur, Head of BPD, in Blumbungan Village. To strengthen the results of these findings, the researcher uses secondary data by analyzing documents or literature related to village asset management. The results of the research findings reveal a fact that the administration in Blumbungan Village has entered asset management practices that are in line with established formal provisions and regulations. However, the principles of sharia accounting that have been applied remain insufficiently articulated. In practice, the treatment, recognition, measurement, presentation, and disclosure of assets continue to be influenced by conventional government accounting standards. Furthermore, significant differences remain between these practices and the core values ​​inherent in Islamic accounting, such as monotheism, trustworthiness, justice, transparency, and accountability. These differences are exacerbated by various challenges, including limited understanding of Islamic accounting concepts among Blumbungan Village officials, the absence of Sharia-based technical regulations, and constraints related to human resource capacity and information technology infrastructure in Blumbungan Village. In the discussion section, this study advocates for the incorporation of Islamic accounting values ​​into village asset management. This can be achieved through implementing training initiatives for Blumbungan Village personnel, developing Sharia-compliant technical guidelines, and improving the monitoring system with active community participation. Through these steps, Blumbungan Village asset management will not only meet administrative requirements but also be aligned with Sharia principles that foster moral values ​​and social responsibility.